Situation Report: Czechoslovakia, 14 March 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Resignations of Slovak National Council Chairman Conservatives Demand Early CC Session More Ministers under Fire USSR Criticized for Silence CSSR Unwilling to Cooperate with Polish Dogmatists